TECHNOLOGIES FOR DEVELOPING STUDENTS' LOGICAL THINKING IN MATHEMATICS LESSONS (International Congress on Economics, Management and Business Studies, 2026)
This scientific article investigates the system of developing students' logical thinking in mathematics lessons of secondary education institutions through the prism of modern pedagogical technologies. The paper scientifically substantiates the functional capabilities of problem-based learning, heuristic methods, and cognitive visualization technologies in forming students' mental operations such as analysis, synthesis, comparison, and generalization. In the course of the study, a set of non-standard and integrated tasks that develop logical thinking was identified, and their effectiveness was analyzed using a pedagogical experiment. The text of the article systematically describes conceptual methodological recommendations for increasing the flexibility of students' mathematical thinking.
Keywords: Logical thinking, cognitive technologies, problem-based learning, mathematical conceptualization, non-standard problems, heuristic approach, mental operations, didactic system.